The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1807-57622013.0371
|View full text |Cite
|
Sign up to set email alerts
|

Gestão em rede e apoio institucional: caminhos na tessitura de redes em saúde mental no cenário regional do Sistema Único de Saúde (SUS)

Abstract: Este relato é um registro cartográfico do apoio institucional junto a uma Secretaria Estadual de Saúde na articulação da rede regional de Saúde Mental. O apoio institucional é uma estratégia da Política Nacional de Humanização nas redes de atenção à saúde e dispositivo de fomento de espaços de cogestão. O relato está pautado em três eixos: a produção de coletivos e os afetamentos dos encontros entre gestores e trabalhadores; a ação articuladora do apoio institucional, as ofertas na análise e a implicação coleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Without the theoretical support provided by strategies of permanent education in the services, based on criticism and reflection in the teaching/learning process, the tendency of the institutions that work in the context of mental health would be the use of the asylum apparatus during the care provided (26) . Thus, it is necessary to turn our attention to the way in which mental health actions are operationalized, contributing to the service redefining its practices and making its intervention power more flexible in psychiatric emergencies (27) . In particular, the training of the Permanent Education Nucleus (NEP) of SAMU-Mossoró may be open to this need and not focus the activities developed in the transmission of knowledge and techniques in a traditionalist perspective of the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…Without the theoretical support provided by strategies of permanent education in the services, based on criticism and reflection in the teaching/learning process, the tendency of the institutions that work in the context of mental health would be the use of the asylum apparatus during the care provided (26) . Thus, it is necessary to turn our attention to the way in which mental health actions are operationalized, contributing to the service redefining its practices and making its intervention power more flexible in psychiatric emergencies (27) . In particular, the training of the Permanent Education Nucleus (NEP) of SAMU-Mossoró may be open to this need and not focus the activities developed in the transmission of knowledge and techniques in a traditionalist perspective of the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some superficiality or tangency is observed, which can also be understood as a lack of knowledge about mental health care priorities in the current care policy, restricting their focus to the existence of the CAPS as something ordinary and uncritical. Another study observed the use of disparate strategies of decentralization and regionalization, with a focus on municipalities (isolated local systems), without a regional and systemic approach, and a delayed emphasis on regionalization in the national health policy (18) .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the RPS was built without hierarchy, using an endless wheel method (17) , to handle the new approaches of process management with technical support, building and strengthening dialogue, personal and affective and institutional bonds, appreciation of articulators and workers, among others 18 , causing this distance based on what affected the managers, workers and the work process in psychosocial care.…”
Section: Discussionmentioning
confidence: 99%
“…As ações de mediação em saúde, pensadas nesse sentido, aproximam-se do apoio institucional, tendo em vista o aparecimento desta função e as contribuições com a expansão do sistema de saúde e com a tessitura de redes que promovam autonomia na gestão dos processos de trabalho e dos serviços (Almeida;Aciole, 2014). Esta função concretiza-se, nas RAS, a partir da figura do articulador, descrita pelos autores citados como sendo alguém externo às equipes que tem a função de atuar em prol de alguma política ou de uma atividade específica.…”
Section: Introductionunclassified